Text and context of the songs of GLOC9 (2003-2012) - Alorro, Mary Joanne F.; Sevillano, Kristine Charisse (2013.)
This descriptive study was conducted to ascertain the text and context of the songs of Gloc9 from 2003-2012. Forty (40) songs with societal issues were determined, classified to which presidential term (Arroyo's or Aquino's) they were released and analyzed if they reflect the real Philippine setting at the given period. The results showed that many of the songs of Gloc9 did not exactly reflect the real-life setting of Filipinos under the two presidential eras they belonged thus as a medium, the songs created a Constructed Mediated Reality. However, songs that mentioned issues such as poverty, unemployment, abuse of power and drug abuse were reflective of period they were written. Nevertheless, rap song is a good medium not only for entertainment but also for information. It is one of the most effective medium to bring awareness to the public by presenting relevant societal issues in a rap music format. To further improve this study, future researchers should do a triangulated research method.
Thesis (Undergraduate, Bachelor of Arts in Communication and Media Studies) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Gloc9 -- Text; Gloc9 -- Context